Bohemian school humanism and its editorial practices : (ca. 1550 - 1610) - Storchová, Lucie (2014)
This volume concentrates on the treatment of classical texts for educational purposes in Bohemia in approximately the 1550s–1620s. This specific – in comparison with other Western European countries, rather 'average' – type of school humanism was characteristic for the literary field which formed around Prague University. In it, a particular form of Melanchthonian Ciceronianism was practised which was adopted by a group of Bohemian humanists during their studies at Saxon universities in the 1530s and 1540s and lasted in a relatively rigid form until the central academic institution was closed in 1622. Such a stability of literary techniques – based also on an unchanging, institutionally passed-down corpus of teaching manuals and school editions – influenced a series of phenomena, including the communication code used by Czech humanists and the fact that the literary field of Prague University was relatively closed and only partly compatible with other contemporary humanist networks on the European continent. Beside the introductory study, the volume includes bibliographical sketches of Czech humanist scholars and an extensive edited section which presents paratexts (for the most part introductory poems and forewords) of the period’s teaching manuals and humanist editions of classics for school needs.